PSYCHOLOGICAL PREPARATION OF YOUNG BOXERS - Turdimurodov Dilmurod Yuldashevich (Journals Park Publishing, 2024)
This article discusses analytical and practical methods of preparing young boxers for the competitive process. Some features of the approach to the psychological preparation of an athlete preparing to perform at boxing competitions are described. The positive effect of the correctly chosen methodology and approach to the psychology of a boxer on his athletic performance, health and personality as a whole.
Keywords: boxing, preparation, psychology, competitions, athletes.